Influence of Inbreeding on the Carabelli Trait in a Human Isolate - Tomislav Lauc (Dental Anthropology Association, 2003)
The purpose of this study is to evaluate the influence of increased homozygosity due to inbreeding on the phenotypic distribution of the Carabelli trait. The sample consisted of 224 dental casts representing 20.2% of the total children aged 7 to 14 years from the endogamous, inbred population of the Island of Hvar, Croatia. Inbreeding analysis compared the children with different rates of grandparental endogamy relative to the expression of Carabelli's trait. The design evaluated the effect of inbreeding on Carabelli trait on the maxillary permanent first molar within a natural setting of reduced variability of environmental factors. Very high frequency of the Carabelli trait was observed for the permanent first molar on both sides of the arcade (84% and 86% on left and right sides). Significant difference among the groups who have different degrees of inbreeding was found when Carabelli trait was divided into absent, negative features, and a positive cusp using Dahlberg's grading system. It seems that Carabelli's trait is strongly genetically determined, and present findings imply it may be controlled by recessive alleles. If heterogeneous polygenic developmental modules are responsible for the diversity of Carabelli's trait, they stay relatively stable after initiation of the developmental process when it appears that other environmental factors have no measurable effect.